Pengembangan Media Magic Letter Pinwheel Untuk Meningkatkan Pelafalan Suku Kata Pada Anak Usia Dini - Denanda, Dewi; Jazuly, Ahmad; Ashadi, Firman (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
The lack of instructional media utilization has resulted in less active and suboptimal learning processes, particularly in syllable pronunciation among early childhood learners. Young children tend to learn through play; therefore, engaging learning media are needed to enhance their participation. This study aims to develop the Magic Letter Pinwheel as an alternative instructional medium to support syllable pronunciation for Group B children at TK Dharma Wanita 03 Lojejer, Wuluhan Subdistrict, Jember Regency. The research employed a research and development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques included observation, interviews, questionnaires, tests, and documentation. The research subjects were Group B students, with assessments conducted by three validators: a media expert, a material expert, and a learning expert. The development process followed the ADDIE stages and utilized easily accessible materials. Validation results indicated a feasibility score of 95%, categorized as highly appropriate. Improvements in children's pronunciation skills were observed, with pretest scores at 80% and posttest scores at 90%, reflecting a 13% increase. Therefore, the Magic Letter Pinwheel is considered effective for enhancing syllable pronunciation skills in early childhood education.